(untitled) (Applied Biological Research, 2012)
The present study was undertaken to evaluate the performance of transplanted rice and direct seeded rice (DSR) as crop establishment methods under different weed control practices. Transplanting method proved superior over DSR. Among the weed management practices, butachlor (1.5 kg a.i. ha-1) + almix (4 g a.i. ha-1) proved superior over other weed management practices with respect to grain yield and yield attributes. Maximum grain yield weed control efficiency was recorded in transplanted rice with the application of butachlor @ 1.5 kg a.i. ha-1+ almix @ 4 g a.i. ha-1.